1712 Serum Electrolytes Variations in Treated Patients with Moderate Asthma Exacerbation. (October 2012) - Neamtu, ML; Brumar, AC
Abstract : Background: Salbutamol induces stimulation of beta2 -receptors resulting in hypokalemia. Corticosteroids also induce plasma electrolytes variations. Aims: To identify blood electrolytes changes following low dose inhaled short-acting beta2 -agonists; To evaluate if concomitant inhaled corticosteroids treatment can amplify serum electrolytes changes. Methods: We analyzed all children admitted for moderate asthma exacerbation during 6 months period. Inclusion criteria: children between 5–18 years of age; PEF >50–75% of predicted value; serum electrolytes normal ranges. Exclusion criteria: previously treated patients with Salbutamol; Salbutamol hypersensitivity; asthma exacerbation severity levels. The patients were divided into 2 groups: 1 st group comprised those treated with beta2 -agonists and 2 nd group is represented by paediatric patients concomitantly treated with beta2 -agonists and corticosteroids. Both groups were homogenous regarding age and sex ratio. During hospitalization, patients received standard low dose of Salbutamol by metered dose inhaler (MDI) and inhaled Fluticasonum propionate using spacer device with mouthpiece. Included patients were assessed for electrolytes serum levels before treatment and 72 hours after therapy. Data was analyzed statistically using independent sample T test, skewness, kurtosis. Results: Among 269 admitted patients, 175 children fulfilled inclusion criteria. Both groups structure: 92 children in 1 st group, 83 in 2 nd group. Authors found for both groups a significant decreasing of serum kalium after beta2 -agonists treatment (p value=0, 010). The study didn't confirm a significant variation of serum electrolytes in 2 nd group as compare to 1 st group. Conclusions: Study confirmed significant hypokalemia after 72 hours inhaled treatment with beta2 -agonists; corticosteroids didn't modify kalium level in association with beta2 -agonists.